KAUSA KEJAHATAN DAN UPAYA PENANGGULANGAN TINDAK PIDANA PENCURIAN TANAMAN PORANG (Studi Yuridis Kriminologis di Desa Sumber Bendo dan Klangon Kecamatan Saradan, Kabupaten Madiun) - Prija Djatmika Sri Lestariningsih Setiawan Nurdayasakti (Masalah-Masalah Hukum, 2010)
Economics problems among society become complicated at the moment. Economic problems, especially poverty, can stimulate the people to commits crimes, such as theft. An example of this statement is a theft of "Porang" plantation that happened in the villages of "Sumberbendo and Klangon" Saradan- Madiun Regency. Economic factor, especially poverty, is the factor of the theft. The criminals commits the theft, in the case, to overcome their daily needs. Besides, environment and lack of social control are also some other factors of the theft. There is a certain kind of models that can be implemented to solve the problem. That is the combination between preventive method and represive method. These two kinds of methods must also be supported by the efforts of formal leaders and the informal leaders. The formal leaders have the authority to enforce the law. To prevent the people commits the crime.